Biological reduction and removal of Cr(VI) with microbial consortia collected from local water treatment plant. (24th December 2014) - Gagrai, Mahesh Kumar; Das, Chandan; Golder, Animes Kumar
Application of microbes in water treatment is a well-established technique. A few microbes are tolerant to toxic heavy metals. Cr(VI) tolerant microbes have practical importance of detoxifying Cr(VI) to Cr(III). The water treatment plant situated at Indian Institute of Technology Guwahati (IITG), India, employs both physical and biological processes to treat domestic wastewater. The microbial consortia collected from this plant is employed to investigate Cr(VI) reduction to Cr(III) and removal behaviour from model effluent. The results reveal that microbial consortia efficiently grow at wide pH range from 4 to 10. Microbial growth is inhibited even with addition of 5 mg L –1 Cr(VI) to the nutrient media over the entire pH range. Reduction efficiency of Cr(VI) to Cr(III) increases with decreasing solution pH, while total chromium removal is higher at elevated pH. Maximum chromium removal is achieved at initial pH of 6. Higher pH may result in Cr(III) precipitation. Therefore, chromium removal is possibly the combined effect of precipitation as well as bioaccumulation.